Impact of digital greening synergistic transformation on urban economic resilience in China: Evidence from quasi-natural experiments - Liangen Zeng; Meiyu Wen; Chengming Li; Yang Nie; Saige Wang (Humanities & Social Sciences Communications)
Abstract Digital greening synergistic transformation (DGST) has emerged as a crucial driver of high-quality economic development, notably enhancing urban economic resilience. This paper examines panel data from 280 Chinese cities (2008–2021) by performing quasi-natural experiments from the ‘Broadband China’ and ‘Low-Carbon Cities’ pilot initiatives and employing a multi-period difference-in-differences (DID) approach. The main findings are as follows. (1) DGST notably enhances urban economic resilience, showing stronger effects than standalone pilot projects. (2) DGST strengthens economic resilience by enhancing defence, adaptation and learning capacities through labour absorption, industrial structure optimisation and green technology innovation. (3) The effect of DGST on economic resilience is influenced by factors such as human capital, financial resources and infrastructure, with cities possessing greater resources deriving more substantial benefits. (4) Cities that implemented ‘Low-Carbon Cities’ prior to ‘Broadband China’ experienced more pronounced improvements in economic resilience. This paper underscores the synergy between digital and green policies in strengthening economic resilience and provides recommendations to advance DGST and strengthen urban economies.